Monitoring Damage Progression in Tensile Tested SiCp/Al Composites Using Acoustic Emission - Wu, Weiguo; Wei, Wei; Wang, Yanju; Sha, Aixue; Hao, Wenfeng (Frontiers in Materials, 2022)
In this paper, the tensile tests of SiCp/Al composites were carried out, and the AE method was used to monitor the damage progress. The collected signals were analyzed in time-frequency domain. The AE signals were analyzed by PCA and FCM to characterize the damage mode and failure mechanism of SiCp/Al composites. Three main damage modes of SiCp/Al composites were identified by FCM clustering: SiC/ Al interface debonding, Al fracture and SiC particle fracture. After the tensile test, the fracture surface was analyzed by SEM. The results of SEM and energy spectrum analysis confirmed the results of acoustic emission. The research results of this paper provide experimental support for the design and engineering application of SiCp/Al composites.